ANALISIS IMPLEMENTASI TEORI KONSTRUKTIVISME DALAM PEMANFAATAN MEDIA GAMIFIKASI TERHADAP KEAKTIFAN BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 40 SERAM BAGIAN TIMUR - Intan Gemelia Fau; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze in depth the implementation of constructivist theory in the use of gamification media to enhance the learning activeness of seventh-grade students in Islamic Education at SMP Negeri 40 Seram Bagian Timur. This research is motivated by the low level of student activeness in learning processes that are still dominated by conventional teaching methods, which have not fully encouraged students’ cognitive, affective, and social engagement. This study employs a qualitative descriptive approach with a case study method. The participants of this study were seventh-grade students. Data were collected through classroom observations, interviews, and documentation. The data were analyzed using thematic analysis based on the constructivist perspective, particularly focusing on social interaction and experiential learning. The findings reveal that the implementation of gamification significantly improves students’ learning activeness. This improvement is reflected in students’ active participation in discussions, increased social interaction, and enhanced learning motivation. Gamification provides a contextual and interactive learning experience, enabling students to construct knowledge independently through collaborative activities. However, this study also identifies several challenges in its implementation, such as limited technological literacy and the lack of optimal instructional design in gamification-based learning. This study recommends a more systematic integration of constructivist theory and gamification technology in instructional practices, as well as the enhancement of teachers’ competencies in designing innovative technology-based learning to improve students’ learning activeness.